Isolation, characterization and pathology of citrobacter freundii infection in native Brazilian catfish Pseudoplatystoma - de Pádua, Santiago Benites; Marques, Debora Peixoto; Sebastião, Fernanda Alexandre [UNESP]; Pilarski, Fabiana [UNESP]; Martins, Maurício Laterça; Ishikawa, Márcia Mayumi (My University, 2014)
Bacterial diseases are responsible for important economic losses in aquaculture over the world, and South American catfishes are susceptible to Gram negative bacteria causative of haemorrhagic septicemia. This study registers the biochemical characteristics, antimicrobial resistance and pathological effects of Citrobacter freundii infection in cachara Pseudoplatystoma reticulatum. Moribund juvenile fish with non-specific clinical signs were used for bacteriological and parasitological diagnosis. No parasitic infections were found in examined fish, but two isolate obtained from the kidney and encephalon was characterized by Gram negative bacilli, catalase positive and oxidase negative. Isolates were submitted to biochemical identification by a commercial API 20E. Susceptibility analysis to 15 drugs was performed by the diffusion method in Agar Muller Hinton discs. Experimental assay was also made to confirm the Kock postulate. The isolates showed biochemical profile corresponding to Citrobacter freundii. A multiresistance at 66.7% of the antibiotic molecules tested was observed. In experimental infection haemorrhagic septicaemia, severe enteritis and important lesions in kidney and gills are described.
Keywords: Antimicrobial resistance; Enterobacteriaceae; Hemorrhagic septicaemia; Siluriformes